Inactivation of chromatin remodeling factors sensitizes cells to selective cytotoxic stress - Freeman MD (Dove Medical Press, 2014)
Miles D Freeman, Tryphon Mazu, Jana S Miles, Selina Darling-Reed, Hernan Flores-Rozas College of Pharmacy and Pharmaceutical Sciences, Florida A&M University, Tallahassee, FL, USA Abstract: The SWI/SNF chromatin-remodeling complex plays an essential role in several cellular processes including cell proliferation, differentiation, and DNA repair. Loss of normal function of the SWI/SNF complex because of mutations in its subunits correlates with tumorigenesis in humans. For many of these cancers, cytotoxic chemotherapy is the primary, and sometimes the only, therapeutic alternative. Among the antineoplastic agents, anthracyclines are a common treatment option. Although effective, resistance to these agents usually develops and serious dose-related toxicity, namely, chronic cardiotoxicity, limits its use. Previous work from our laboratory showed that a deletion of the SWI/SNF factor SNF2 resulted in hypersensitivity to doxorubicin. We further investigated the contribution of other chromatin remodeling complex components in the response to cytotoxic chemotherapy. Our results indicate that, of the eight SWI/SNF strains tested, snf2, taf14, and swi3 were the most sensitive and displayed distinct sensitivity to different cytotoxic agents, while snf5 displayed resistance. Our experimental results indicate that the SWI/SNF complex plays a critical role in protecting cells from exposure to cytotoxic chemotherapy and other cytotoxic agents. Our findings may prove useful in the development of a strategy aimed at targeting these genes to provide an alternative by hypersensitizing cancer cells to chemotherapeutic agents. Keywords: chromatin remodeling, cancer, DNA damage/repair, heat-shock response, oxidative stress